Effects of different land-use managements on soil fertility status in Rift Valley Areas of Gamo-Konso Massifs, Ethiopia - T.A. Yadda; D.A. Zebire (Journal of Applied Sciences and Environmental Management, 2019)
Understanding soil properties and their productiveness under different land use management have proved to be useful for sustainable development and efficient utilization of limited land resources. A systematic soil survey was made for the first time in the Ethiopian Rift valley flat plain areas of Gamo-Konso Massifs. The objectives were to: (1) identify the land uses and their role on soil physicochemical properties under varying climatic conditions; (2) assess the nature and extent of soil salinity problems; (3) identify best land use management practices. Annual crops (AA); perennial crops (AP), and Natural Forest (NF) land-uses were identified. The result showed organic carbon (OC) and total nitrogen (TN) were varied along different land uses. Generally, OC, TN, percentage base saturation, exchangeable (potassium, calcium and magnesium), available, phosphorus (P2O5), manganese, copper and iron contents decreased in cultivated areas. The AA has less nutrient content compared to AP in irrigated agriculture while in AP it is greater than AA under rainfed. Clay, TN, P2O5 and available potassium (K2O) contents were correlated positively and highly significantly with OC and electrical conductivity (EC). In conclusion, the study revealed that most of the soil properties are influenced by land use management. Therefore, it could be recommended to include management practices that increase OC and TN in the system, when the land is continuously cultivated. Reclamation of the areas should start by    considering available options like crop rotation as a good means of management.